Marketing musicscapes, or the political economy of contagious magic. (April 2014) - Roberts, Les
The economic imperatives that have driven, with various shades of success, urban regeneration initiatives in post-industrial towns and cities in the United Kingdom have sought to capitalise on a music and cultural heritage predicated on an intrinsic embeddedness in the place of the local. Building on discussions around popular musicscapes and local distinctiveness, this article explores the contention that the appeal of popular music heritage from a tourism and place-marketing perspective can in part be attributed to the 'contagious magic' factor: the tapping of symbolic value associated with well-known musicians and the interweaving of these narratives into the wider place-myths attached to particular locations as part of boosterist and regeneration strategies. Alongside celebrity-oriented 'contagion' as an efficacious tool of alchemical place branding, 'sympathetic magic', its anthropological twin, is ritually enacted in embodied and performative iterations of music and place, including music tourism and heritage trails, studio tours, and tribute acts. Drawing on research conducted into popular music heritage tourism in the United Kingdom, this article explores links between cultural heritage, consumption and place by examining the extent to which the 'rubbing off' of musical cultural capital can be said to have informed the development of a political economy of contagious magic.